2007
DOI: 10.1080/09687860601070806
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression and kinetic modeling of substrate interactions of a uracil transporter inAspergillus nidulans

Abstract: Early genetic evidence suggested that A. nidulans possesses at least one uracil transporter. A gene, named furD, was recently identified by reverse genetics and in silico approaches and we confirm here that it encodes a high-affinity, high-capacity, uracil transporter. In this work, we study the regulation of expression of FurD and develop a kinetic model describing transporter-substrate interactions. The furD gene is not expressed in resting conidiospores, is transcriptionally activated and reaches a peak dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 32 publications
4
43
0
2
Order By: Relevance
“…In agreement with transport assays, epifluorescence microscopy of germlings of a strain carrying a UreA-GFP fusion shows that the appearance of fluorescence in the membrane occurs also after 2 h of culture (not shown). Interestingly and at variance to what has been observed for other transporters (Amillis et al, , 2007Tazebay et al, 1997), uptake of urea is repressed by ammonium during the period of conidial isotropic growth. No saturable [ 14 C]-urea uptake was detected at any stage or N-source in the DureA strain.…”
Section: Urea Deletion and Characterization Of Urea1 And Urea905 Mutamentioning
confidence: 40%
See 1 more Smart Citation
“…In agreement with transport assays, epifluorescence microscopy of germlings of a strain carrying a UreA-GFP fusion shows that the appearance of fluorescence in the membrane occurs also after 2 h of culture (not shown). Interestingly and at variance to what has been observed for other transporters (Amillis et al, , 2007Tazebay et al, 1997), uptake of urea is repressed by ammonium during the period of conidial isotropic growth. No saturable [ 14 C]-urea uptake was detected at any stage or N-source in the DureA strain.…”
Section: Urea Deletion and Characterization Of Urea1 And Urea905 Mutamentioning
confidence: 40%
“…[ 14 C]-urea uptake in minimal media (MM) was assayed in germinating conidiospores of A. nidulans concentrated at 10 7 conidiospores/100 lL, at 37°C, pH 6.8, as previously described (Amillis et al, 2007;Cecchetto et al, 2004;Papageorgiou et al, 2008). Initial velocities were measured at 1-2 min of incubation substrates.…”
Section: Radiolabelled Urea Uptake Measurementsmentioning
confidence: 99%
“…When one gene is involved in more than one step, the complete entry is shown once and only the gene symbol and database entry is shown opposite additional steps. Experimental identification of each gene is described in: nadA (Ribard et al, 2003); hxA (Glatigny and Scazzocchio, 1995); hxB (Amrani et al, 1999(Amrani et al, , 2000; xanA (Cultrone et al, 2005); uaZ ; azgA (Cecchetto et al, 2004); uapA (Gorfinkiel et al, 1993); uapC (Diallinas et al, 1995); fcyB (Vlanti and Diallinas, 2008); furD (Amillis et al, 2007;Hamari et al, 2009); furA (Hamari et al, 2009); ureA (Abreu et al, 2010); uaX and uaW are described in this article. alX (Hamari et al, 2009) aaX and the putative ureidoglycolase gene were identified by similarity with the cognate genes of S. cerevisiae, confirmed for alX and aaX by their known chromosomal locations.…”
Section: Strainsmentioning
confidence: 98%
“…In response to exogenous uracil, the transcriptional level of FUR4, which encodes a uracil permease for uracil transport in S. cerevisiae [12], is downregulated [13,14]. Similarly, exogenous uracil triggers the transcriptional down-regulation of A. nidulans furD, a gene encoding Fur4p-like uracil permease [15]. At the posttranslational level, the presence of exogenous uracil accelerates the degradation of Fur4p by enhancing its ubiquitylation [14].…”
mentioning
confidence: 99%
“…At the posttranslational level, the presence of exogenous uracil accelerates the degradation of Fur4p by enhancing its ubiquitylation [14]. Tight control of the cellular uracil level is believed to be important to maintain a low ratio of uracil/thymine to prevent the incorporation of uracil into DNA [15]. Replacement of thymine with uracil in regulatory regions of genomic DNA can disrupt the specificity of protein-DNA interactions [16].…”
mentioning
confidence: 99%